2007
DOI: 10.1188/07.onf.869-876
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Japanese Patients With Colorectal Cancer During the First Six Months After Surgery

Abstract: Some of the patients were sincere and skillful in asking for help to live normal lives, but others found that difficult. The present findings are significant in helping nurses provide interventions to enable patients to make use of assistance or support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 19 publications
0
36
0
12
Order By: Relevance
“…Physiologically, patients have been found to experience fatigue six months following treatment for colo‐rectal cancer (Mizuno et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Physiologically, patients have been found to experience fatigue six months following treatment for colo‐rectal cancer (Mizuno et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition to symptom evaluations on cause, severity and temporality, these studies showed that patients make judgements about their ability to achieve control and if their symptoms can be cured (Mizuno et al . , Kidd et al . , Beaver et al .…”
Section: Introductionmentioning
confidence: 99%
“…We make sense of that which is lived through. 14 Interpretive inquiries related to living with gastroin-testinal cancer have focused on areas such as being given a diagnosis, 15 recovery from surgery, 16 sense making in illness, 17 surviving treatment, 18 surgical treatment for metastases, 19 alleviation of suffering, 6 and human learning at the end of life. In this way, sense making is both socially and culturally embedded.…”
mentioning
confidence: 99%
“…[16] The questionnaire is composed of 16 items assessing demands including “managing my own daily activities according to my physical condition,” “communicating my own needs to my family/friends,” “establishing a lifestyle that adapts to my present state,” and “understanding what medical information I actually need.” The items were presented using a 5-point Likert scale ranging from “strongly disagree” to “strongly agree.” Higher scores indicated a greater perception of demands. A previous study on patients with cancer of the gastrointestinal tract and other cancer sites confirmed that the instrument exhibited strong internal consistency (α = 0.77).…”
Section: Methodsmentioning
confidence: 99%